USING DIRECTED READING ACTIVITY (DRA) METHOD ON STUDENTS’ READING COMPREHENSION - abdullah hasan (Indonesian Journal of Integrated English Language Teaching, 2018)
The aim of this study is to find out the effect of using Directed Reading Activity (DRA) Method on students’ reading comprehension. The research design was a quasi-experimental study using pre-test and post-test non-equivalent control group design. The participants of the study consisted of 63 students divided into an experimental group (31) and a control group (32) of the students of MAN 1 Pekanbaru. Two research questions and four hypotheses were posed in this study. Pretest and posttest were administered in this study and independent and dependent sample t-tests were used to analyze the data. The research finding showed a significant effect of using Directed Reading Activity (DRA) method on students’ reading comprehension. Using DRA method contributed 76% on students’ reading comprehension, meanwhile the control group using non-DRA method contributed 49%. At last, it can be inferred that DRA method is suitable to apply in teaching reading comprehension at State Islamic Senior High School (MAN) 1 Pekanbaru.